2006
DOI: 10.1086/505976
|View full text |Cite
|
Sign up to set email alerts
|

Use of Vancomycin-Containing Lock or Flush Solutions for Prevention of Bloodstream Infection Associated with Central Venous Access Devices: A Meta-Analysis of Prospective, Randomized Trials

Abstract: Use of a vancomycin lock solution in high-risk patient populations being treated with long-term central IVDs reduces the risk of BSI. The use of an anti-infective lock solution warrants consideration for patients who require central access but who are at high risk of BSI, such as patients with malignancy or low-birthweight neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(48 citation statements)
references
References 97 publications
(124 reference statements)
1
47
0
Order By: Relevance
“…77 In addition, vancomycin locks have been found to increase risk for selecting gram positive bacteria with reduced susceptibility to vancomycin. 78 Ethanol locks are attractive options for adjunctive therapy for CLABSI given that ethanol readily penetrates biofilm, has thrombolytic and anticoagulant properties, and has activity against both bacteria and fungi without promoting emergence of antimicrobial resistance. However, ethanol locks are generally restricted to patients with silicone-based CVCs based upon concerns for possible mechanical complications when used in polyurethane catheters.…”
Section: Antimicrobial Therapy For Mdr Pathogens-carbapenem-resistantmentioning
confidence: 99%
“…77 In addition, vancomycin locks have been found to increase risk for selecting gram positive bacteria with reduced susceptibility to vancomycin. 78 Ethanol locks are attractive options for adjunctive therapy for CLABSI given that ethanol readily penetrates biofilm, has thrombolytic and anticoagulant properties, and has activity against both bacteria and fungi without promoting emergence of antimicrobial resistance. However, ethanol locks are generally restricted to patients with silicone-based CVCs based upon concerns for possible mechanical complications when used in polyurethane catheters.…”
Section: Antimicrobial Therapy For Mdr Pathogens-carbapenem-resistantmentioning
confidence: 99%
“…The infection due to these external-internal devices may be localized to entrance-site and/or tunnel (or port-pocket in the case of port-a-cath CVC) and, when associated to SIRS, is the cause of device-associated "blood systemic infection" (BSI). Cancer patients with implantable port systems experienced a median of 0.2 infections per 1000 catheter-days (range: 0-2.7 per 1000 catheter-days) [134] versus a risk that ranges from 1.4 to 2.2 infections per 1000 catheter-days for subcutaneous tunneled CVCs [135,136]. Nevertheless, this difference may be biased by the fact that patients who receive implantable subcutaneous ports usually receive much less intensive cancer therapy [137].…”
Section: -The Evaluation Of the Suspected Infection Sourcementioning
confidence: 99%
“…Another prevention strategy is the use of gentamicin, cephalosporin or vancomycin lock solution, taking into account the possibility of the emergence of resistant microorganisms when vancomycin is used (19) . In a meta-analysis, authors demonstrated that in highrisk patients treated with long-term catheters the use of vancomycin lock solution reduces the risk of bacteremia (20).…”
Section: Resultsmentioning
confidence: 99%